247. Catching CAPA: The Healthcare Impact of COVID-19-Associated Pulmonary Aspergillosis in an Academic Medical Center. (15th December 2022) - Hamilton, Caroline; Tran, Sarah; Dinh, Judy; Askar, Gina; Askar, Gina; Askar, Gina; Askar, Gina
Abstract: Background: COVID-19 associated pulmonary aspergillosis (CAPA) is a known complication of COVID-19 which carries a high mortality rate. While there are proposed diagnostic criteria, CAPA remains likely underdiagnosed. Our objectives are to evaluate markers of disease severity, bacterial coinfections, and outcome measures in order to assess the clinical impact of CAPA in patients admitted with COVID-19. Methods: A retrospective chart review was performed on all adult patients admitted to a single-center, tertiary hospital from March 1, 2020 to May 1, 2022 with a positive COVID-19 PCR and probable or proven CAPA based on ECMM/ISHAM consensus criteria. Admission data, ICU status, time to CAPA diagnosis, respiratory cultures, and 90-day mortality were identified. Results: 14 patients met criteria for probable CAPA. 10 of 14 patients (71.4%) were immediately admitted to the ICU. By day 14, 13 patients (92.9%) were intubated. The average time from admission to CAPA diagnosis was 31.3 days. 12 patients were diagnosed by BAL galactomannan, while 2 patients were diagnosed by growth on respiratory culture. 12 patients (85.7%) also had bacterial growth on respiratory cultures. The most common pathogen was Staphylococcus aureus, which was seen in 6 patients. All-cause mortality was 42.8%, or 6 of 14 patients, at day 90. In patients with a CAPA diagnosis, the average length of ICU stay was 36.4 days and average total hospital length of stay was 43.6 days, compared to 6.3 and 12.5 days, respectively, for all patients admitted with COVID-19 disease. Conclusion: CAPA is a rare complication of COVID-19 but had substantial negative impacts on affected patients. The late onset of CAPA may be a result from longer hospitalizations and increased healthcare-associated infections. The association of CAPA with bacterial coinfections is consistent with literature on other viral infections such as influenza predisposing to secondary pneumonias. As the majority of cases were diagnosed by galactomannan rather than culture, providers should have a low threshold for testing in patients with protracted hospitalization for COVID-19. This case series emphasizes the poor outcomes associated with CAPA and its burden on already strained hospital resources, highlighting the need for improved disease awareness and further study. Disclosures: All Authors : No reported disclosures.